A adesão das instituições privadas ao PROUNI : interesses em pauta - Silveira, Grazielle Vital da (2013)
This research aimed to highlight the interests of the private sector of higher education in joining the program PROUNI, the methodology was based on the historical and dialectical materialism in which qualitative and quantitative methods are inseparable. For the realization of this study used the desk research and interviews. The PROUNI 11.096/2005 was established by law, it is a program that provides scholarships to low-income students in private institutions of higher education, these in return receive tax exemption of certain taxes namely Corporate Income Tax - Income Tax, Social Contribution on Net Income - Social Contribution, Contribution to Social Security Financing - COFINS and Social Integration Program - PIS. Considered the political and economic context that has influenced this policy, and basing on the historical recollection of Brazilian higher education, we tried to carry out a critical analysis of the PROUNI and interests that involves. First, we sought to understand the changes of the capitalist system in the twentieth century and their influence in Brazilian politics, highlighting the recommendations of international bodies and exposing the duel of the public / private sectors in Brazilian education. Then sets up the legal framework PROUNI highlighting the interests and disputes that permeated. In the third phase analyzed the criticisms made by researchers on the Program. Extracted that scholars address PROUNI with caveats understanding that the program deepens the process of marketization of higher education in Brazil. Finally, we analyzed the data that make up actually showed up and positioning of organizations representing the private sector. Grounded in historical materialism dialectical this research concluded that PROUNI interests to HEI by financial advantages that it bestows upon the tax relief and also for granting the FIES (recast). In summary, it was concluded also that PROUNI is a Brazilian public policy on education, which so favors on private initiative and still creates the illusion of being a cutting-edge education and solving educational problems.